Integrating Deep Learning Approaches to Strengthen Students’ Religious Moderation and Character Formation - Lindriany, Julita; Suyatno; Hartanto, Dody; Putri, Maritza Dita Fiorenza Aprilia; Putri, Phasa Amalia Arzetty (The Indonesian Institute of Science and Technology Research, 2025)
Technological advances in the digital era present both challenges and opportunities in the world of education, especially in efforts to instill religious moderation values in the younger generation. This study aims to analyze how deep learning technology can be integrated into religious education to form a generation with character and tolerance. The method used is a literature review, by collecting and analyzing literature from various academic sources such as journals, books, and research reports relevant to the topics of deep learning, education, and religious moderation. The analysis is done thematically to identify patterns of deep learning utilization in filtering extreme content, providing contextual learning materials, and supporting personalization of religious learning. The results show that deep learning has the potential to be a strategic tool in developing an inclusive and adaptive religious education curriculum. This research recommends the need for collaboration between educators, technology developers, and policy makers in designing technology-based education that remains rooted in moderate values.